Cardiac device therapy in patients with left ventricular dysfunction and heart failure: 'real‐world' data on long‐term outcomes (mortality, hospitalizations, days alive and out of hospital). (6th April 2016) - Boriani, Giuseppe; Berti, Elena; Belotti, Laura Maria Beatrice; Biffi, Mauro; De Palma, Rossana; Malavasi, Vincenzo L.; Bottoni, Nicola; Rossi, Luca; De Maria, Elia; Mantovan, Roberto; Zardini, Marco; Casali, Edoardo; et al.
Abstract : Background: The impact on long‐term outcomes of implantable cardioverter defibrillators (ICDs) and biventricular defibrillators for cardiac resynchronization (CRT‐D) devices in 'real world' patients with heart failure (HF) needs to be assessed in terms of clinical effectiveness. Methods and results: A registry including consecutive HF patients who underwent a first implant of an ICD (891 patients) or a CRT‐D device (709 patients) in 2006–2010 was followed (median 1487 days and 1516 days, respectively), collecting administrative data on survival, all‐cause hospitalizations, cardiovascular or HF hospitalizations, and days alive and out of hospital (DAOH). Survival free from death/cardiac transplant was 61.9% and 63.8% at 5 years for ICD and CRT‐D patients, respectively. Associated comorbidities (Charlson Comorbidity Index) had a significant impact on death/cardiac transplant, as well as on hospitalizations. The median values of DAOH% were 97.4% for ICD and 97.7% for CRT‐D patients, but data were highly skewed, with the lower quartile of DAOH% values including values ranging between 0% and 52.8% for ICD and between 0% and 56.1% for CRT‐D patients. Charlson Comorbidity Index was a very strong predictor of DAOH%. Conclusions: Patients who were implanted in 'real world' clinical practice with an ICD or a CRT‐D device have, on average, a relatively favourable outcome, with a survival of around 62–64% at 5 years, but with an important burden of hospitalizations. Comorbidities, as evaluated by means of the Charlson Comorbidity Index, have a significant impact on outcomes in terms of mortality/heart transplant, hospitalizations and days spent alive and out of hospital.